Suppression of Parathyroid Hormone as a Proxy for Optimal Vitamin D Status: Further Analysis of Two Parallel Studies in Opposite Latitudes - Marcela M. Mendes (Nutrients, 2020)
Optimal vitamin D status has commonly been defined as the level of 25-hydroxyvitamin D (25(OH)D) at which parathyroid hormone (PTH) concentrations would be maximally suppressed, represented by an observed minimum plateau. Previous findings indicate a large variation in this plateau, with values ranging from <30 nmol/L up to 100 nmol/L. This disparity in values might be explained by differences in study design and methodology, ethnicity, age, gender and latitude. This study aimed to investigate the concentration of 25(OH)D at which PTH concentrations were suppressed in Brazilian women living in opposite latitudes (high vs. low: i.e., UK and Brazil), during wintertime. Using data from the D-SOL study (Interaction between Vitamin D Supplementation and Sunlight Exposure in Women Living in Opposite Latitudes), the association between 25(OH)D status and PTH levels were examined in 135 Brazilian women (56 living in England and 79 living in Brazil, aged 20–59 years old). Mean PTH concentrations for Brazilian women with vitamin D deficiency (<25 nmol/L) were significantly higher compared to those with vitamin D insufficiency (25–49.9 nmol/L) (p < 0.01), vitamin D adequacy (50–74.9 nmol/L) (p < 0.01) and those with optimal vitamin D status (>75 nmol/L) (p < 0.001). Regression modelling was used to investigate the relationship between serum 25(OH)D and PTH for the sample as a whole and for each group separately. A cubic model was statistically significant for the total sample (p < 0.001), whereas a linear model presented the best fit for Brazilian women living in England (p = 0.04) and there were no statistically significant models fitted for Brazilian women living in Brazil. The cubic model suggests that 25(OH)D concentrations above 70–80 nmol/L are optimal to suppress the parathyroid gland in Brazilian women. These findings contribute to a better understanding of the relationship between 25(OH)D and PTH in populations living in a low latitude location and are of great relevance for discussions regarding the estimation of optimal cut-offs for vitamin D levels in the Brazilian population as well as for other low latitude locations.